PENGARUH INDEKS PEMBANGUNAN MANUSIA TERHADAP INDEKS KUALITAS LINGKUNGAN HIDUP DI INDONESIA - ANDI TENRI LAWA PUTRI LANRANG HARIS; ANDI DORAWATI ISHAK; ANDI ENTONG; ANDI TENRI ELLYANA HARIS (Universitas Mahasaraswati K. Mataram, 2023)
The human development index is an indicator used to see development progress in the long term. This study uses panel data regression from 34 provinces in Indonesia with a fixed model analysis technique to analyze the effect of economic growth and poverty on the environmental quality index in 2015-2019. The results of the study show that the human development index has a positive and significant effect on the environmental quality index in Indonesia.